2012
DOI: 10.1093/cercor/bhs307
|View full text |Cite
|
Sign up to set email alerts
|

NFIX Regulates Neural Progenitor Cell Differentiation During Hippocampal Morphogenesis

Abstract: Neural progenitor cells have the ability to give rise to neurons and glia in the embryonic, postnatal and adult brain. During development, the program regulating whether these cells divide and self-renew or exit the cell cycle and differentiate is tightly controlled, and imbalances to the normal trajectory of this process can lead to severe functional consequences. However, our understanding of the molecular regulation of these fundamental events remains limited. Moreover, processes underpinning development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(142 citation statements)
references
References 83 publications
(142 reference statements)
7
129
0
Order By: Relevance
“…Previous studies have demonstrated that neural progenitor cells in the hippocampal neuroepithelium express NFIX during development from at least E13.5 onwards (Heng et al, 2014); however, the cell type-specific identity of these cells has not been established. The transition of radial glia to IPCs during development is demarcated by the sequential expression of PAX6 then TBR2 (EOMES) (Englund et al, 2005).…”
Section: Nfix Is Expressed By Radial Glia and Ipcs During Hippocampalmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have demonstrated that neural progenitor cells in the hippocampal neuroepithelium express NFIX during development from at least E13.5 onwards (Heng et al, 2014); however, the cell type-specific identity of these cells has not been established. The transition of radial glia to IPCs during development is demarcated by the sequential expression of PAX6 then TBR2 (EOMES) (Englund et al, 2005).…”
Section: Nfix Is Expressed By Radial Glia and Ipcs During Hippocampalmentioning
confidence: 98%
“…We have previously reported elevated numbers of PAX6 + cells (indicative of increased numbers of radial glial cells) and delayed neuronal differentiation in the hippocampus of Nfix −/− mice at E16.5 (Heng et al, 2014). It remained unclear, however, when these developmental defects first become apparent and which stage of the lineage transition from a stem cell to a mature neuron is affected in these mice.…”
Section: Tbr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NFIX is expressed by a subset of quiescent NSCs in vivo and might play a similar role in regulating their gene expression programs, as we observed in cultured quiescent NS cells. Nfix-null mutant mice present severe morphological defects in both the SEZ and DG at postnatal stages as well as defects in progenitor cell differentiation in the DG at birth (Campbell et al 2008;Heng et al 2012b). They die at 3 wk of age, which precludes an analysis of hippocampal NSCs by label retention, but postnatal hippocampal NSCs can also be identified by their radial morphology and the coexpression of Nestin and GFAP.…”
Section: Nfix Is Required For Nsc Quiescence In the Postnatal Brainmentioning
confidence: 99%
“…Nfix mutants present an overexpansion of the embryonic brain and a delay of hippocampal progenitor differentiation that are not seen in other Nfi mutants (Driller et al 2007;Campbell et al 2008;Heng et al 2012b). Moreover, manipulation of Nfia expression alongside that of Nfix in NS cells shows that the two genes have different activities in the cells, and Nfia does not have a prominent role in the regulation of quiescence (B Martynoga, unpubl.).…”
Section: Nfix Targets Cell Adhesion and Ecm Genes To Promote Ns Cell mentioning
confidence: 99%